Learning in Sequential Wage Negotiations: Theory and Evidence - Kuhn, Peter; Gu, Wulong (Journal of Labor Economics, 1999)
When union‐firm pairs bargain sequentially, and when unobserved components of firms' abilities to pay are subject to correlated shocks, unions that bargain later in a sequence can acquire valuable information by observing previous bargaining outcomes in their industry. We derive the implications of this kind of learning in an asymmetric information model of wage negotiations and argue that the most robust implication is a lower incidence of strikes among “followers” than “leaders” in wage negotiations. Considerable empirical support for this implication is found in a long panel of Canadian contract negotiations.